Pergau Reservoir Information System (PRIS) for mapping and sedimentaion studies: A study on the development of the reservoir database - Abd. Majid, A. K.; Desa, Ghazali; Musa, Tajul A. (1997)
The main part of a hydroelectric project is the dam with its natural or man made lakes or reservoirs. As in the case of many tropical countries, heavy rainfally and effects of upstream changes in landuse have caused detrimental consequences on the sedimentation. Reservoir Information system, therefore, is recognized presetly as the most suitable and efficient tool to manage the reservoir. The present study will focus on Reservoir Information system for the Pergau Hydroelectric Project, which is located in the State of Kelantan, Malaysia. This paper presents the results of the first phase of the study, i.e. on the data sources and data acquisition techniques in order to develop the Pergau Reservoir Database. The Database will be the major component part of the Pergau Reservoier Information System (PRIS).